Representation Criticism of Digital Technology Abuse in @rahma_toons Cartoons: A Semiotic Analysis of Charles Sanders Peirce - Muhajjalin, Ahmad Ghuril; Munjiah, Ma'rifatul; Rohman, Khabib Syaikhu (Mantiqu Tayr: Journal of Arabic Language, 2026)
Digital technology is developing rapidly and undergoing continuous change. Instagram is used as an information center for writing about social issues through cartoon illustrations. Cartoons are a visual way to discuss social phenomena in a humorous or satirical manner. Cartoons contain visual elements that convey meaning. The purpose of this study is to uncover the meaning contained in the cartoons on Instagram @rahma_toons. The methodology used in this study is descriptive qualitative, to determine the representation of @rahma_toons cartoons using Charles Sanders Peirce's semiotic theory, which focuses on three trichotomy concepts. First, identifying relevant cartoons from the Instagram account and additional data from scientific literature sources. Second, presenting data grouped by icons, symbols, and indexes. Next, the results of the analysis are presented in detail. The findings show that cartoons from @rahma_toons convey social criticism of the negative impacts of digital technology through clear visual representations. This study emphasizes the importance of visual media literacy skills to understand critical messages in today's digital era. For further research, it is recommended to expand the object of study, not only on caricatures, and it is also recommended to use approaches from other semiotics, to enrich the perspective of visual meaning analysis.